COVID-19 Associated Ischemic Stroke and Hemorrhagic Stroke: Incidence, Potential Pathological Mechanism, and Management - Wang, Zilan; Yang, Yanbo; Liang, Xiaolong; Gao, Bixi; Liu, Meirong; Li, Wen; Chen, Zhouqing; Wang, Zhong (Frontiers in Neurology, 2020)
The outbreak of the novel coronavirus infectious disease 2019 (COVID-19) caused by the SARS-CoV-2 virus has rapidly spread around the world. Increasing evidence has suggested that patients with COVID-19 may present neurological symptoms, and cerebrovascular diseases are one of the most frequent comorbidities. The markedly elevated D-dimer levels in patients with acute ischemic stroke suggests that SARS-CoV-2 infection may induce an inflammatory response and trigger a hypercoagulation state, thus leading to acute ischemic stroke. Cardioembolism and atherosclerosis in patients with COVID-19 infection may also increase the risk of ischemic stroke. The reduction of the angiotensin-converting enzyme II (ACE2) caused by SARS-CoV-2 binding to the ACE2 receptor can lead to abnormally elevated blood pressure and increase the risk of hemorrhagic stroke. Additionally, the cytokine storm induced by the immune response against the viral infection increases the risk of acute stroke. The management for COVID-19 patients with stroke is not only based on the traditional guidelines, but also based on the experience and new instructions from healthcare workers worldwide who are combatting COVID-19.